Journalistic Photography as a Communication Media for President Jokowi to Spread Covid-19 Vaccination Information - Ahmad Muhyiddin; Hasrullah; Muliadi Mau (GoAcademica Research & Publishing, 2022)
This study analyzes photojournalism on President Jokowi's official account when disseminating vaccine information. This research uses a qualitative approach and analyzes photos using Roland Barthes' semiotics. Researchers found the results of the study that the news photo provided information so that the public followed the government's recommendation for a vaccine so that the pandemic would end soon and the impact of anxiety about fake news related to vaccines should be minimized because the Covid-19 vaccine was tested to be safe and halal.